DEVELOPING E-DICTIONARY AS AN INNOVATIVE MEDIA IN COVID-19 PANDEMIC - Fitria Nur Hamidah; Fadelis Sukya; Dion Yanuarman (University of Muhammadiyah Malang, 2021)
Developing e-dictionary as an innovative online learning media in Covid-19 pandemic is a smart option in learning. It was needed to use in teaching English both online and offline. This research aims at explaining the process of electronic dictionary which is produced as a teaching media to increase learning interest and English language skills in Quin Nabila Tutoring Institution during Covid-19 Pandemic. The subjects of this research were English tutors of Quin Nabila Kediri. This research conducted Research and Development. Moreover, Observation and interviews are the instruments of this research. Furthermore, The results of this research showed that developing E-dictionary gave contributions to teaching English, especially in the use of innovative media in the offline and online learning process during Covid-19 pandemic. This institution needed this dictionary in English teaching because the implication of e-dictionary could help the tutors when they taught their students. Therefore, the use of electronic dictionary was very useful and helpful for Quin Nabila tutoring institution in Covid-19 pandemic.